2006
DOI: 10.1080/019131290969442
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Hyalinizing Angiectatic Tumor of Soft Parts: Ultrastructural Analysis of a Case with Original Features

Abstract: Pleomorphic hyalinizing angiectatic tumor, a rare neoplasm of uncertain lineage resembling malignant fibrous histiocytoma and schwannoma, was first described in 1996 by M. E. F. Smith et al. (Am Surg Pathol. 20:21-29). To date, less than 100 cases have been reported in the international literature. It occurs in subcutaneous and intramuscular soft tissues of extremities or trunk in adults without sex predilection. All lesions are composed of sheets and fascicles of spindled and pleomorphic cells associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The electron microscopic study revealed numerous cytoplasmic granular deposits consistent with hemosiderin, and masses of wavy filaments in the cytoplasm of lesional cells consistent with vimentin filaments (Fig. 3), consistent with previous observations [1,5,7].…”
Section: Figsupporting
confidence: 91%
“…The electron microscopic study revealed numerous cytoplasmic granular deposits consistent with hemosiderin, and masses of wavy filaments in the cytoplasm of lesional cells consistent with vimentin filaments (Fig. 3), consistent with previous observations [1,5,7].…”
Section: Figsupporting
confidence: 91%
“…These cells were abundant, although scattered throughout the tumor, and they were identified as mast cells, which was clearly highlighted in the Giemsa stain (Fig. Apart from neurofibroma, which is the most commonly mentioned in literature, [4][5][6] one can also mention dermatofibroma, 7,8 Gardner fibroma, 9 superficial acral fibromyxoma, 10,11 elastofibroma, 12 pleomorphic hyalinizing angiectatic tumor, [13][14][15] ossifying fibromyxoid tumor, 16 desmoplastic fibroblastoma, 17 cellular hemangiomas, 18 solitary fibrous tumor of oral mucosa, 19 and multinucleated cell angiohistiocytoma. It is well known how mast cells express CD117, which allows these cells to be highlighted in an immunohistochemical study.…”
Section: Letters To the Editormentioning
confidence: 99%
“…PHAT was initially described in 1996 by Smith et al 10 and represents a rare low‐grade neoplasm with fibrous differentiation 11–13 . PHAT most commonly presents in adults as a slow‐growing mass involving the lower extremity and may mimic a hematoma clinically.…”
Section: Hemosiderotic Fibrolipomatous Tumor and Phatmentioning
confidence: 99%